2014
DOI: 10.1007/8904_2014_394
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental and Cognitive Outcomes of Classical Homocystinuria: Experience from Qatar

Abstract: Background: Classical homocystinuria due to cystathionine b-synthase (CBS) deficiency (OMIM 236200) is a recessively inherited condition caused by mutations in the CBS gene. The founder mutation p.R336C accounts for almost all CBS deficiency in Qatar, affecting approximately 1 in 1,800 births, making it the most prevalent monogenic disease among the Qatari population. Untreated patients can have severe intellectual disability (ID), devastating multisystem complications and premature death. Current treatment is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Central nervous system: intellectual, psychiatric and behavioural problems are all common, especially in pyridoxine unresponsive patients (Abbott et al 1987; El Bashir et al 2015). Without treatment, approaching 90 % pyridoxine unresponsive patients have learning difficulties (Mudd et al 1985).…”
Section: Recommendationsmentioning
confidence: 99%
“…Central nervous system: intellectual, psychiatric and behavioural problems are all common, especially in pyridoxine unresponsive patients (Abbott et al 1987; El Bashir et al 2015). Without treatment, approaching 90 % pyridoxine unresponsive patients have learning difficulties (Mudd et al 1985).…”
Section: Recommendationsmentioning
confidence: 99%
“…Similarly, in an earlier study utilizing healthy siblings as controls, showed that patients diagnosed by NBS had better developmental and cognitive outcomes than did those diagnosed later. 19 These results remained significant in the correlation analysis even when we adjusted for current age and age at diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…With a consanguinity rate of 2.38% for all metabolic conditions diagnosable by newborn screening in the IBEM-IS, we are able to provide an additional benchmark for current and future comparisons within a population ascertained by presence of recessive conditions. For comparison, previous studies from other countries have reported consanguinity rates of 5.2% for biotinidase deficiency in Brazil, 74.2% for organic acidemias in Syria, 84% for homocystinuria in Qatar, and 86.9% for 46 different metabolic disorders in Libya (AlObaidy, 2013; Borsatto et al, 2014; El Bashir, Dekair, Mahmoud, & Ben-Omran, 2015; Shennar, Al-Asmar, Kaddoura, & Al-Fahoum, 2015). Given that not all families enrolled in the IBEM-IS may be comfortable reporting consanguinity to care providers, it is possible that the 2.38% figure found in our study is an underestimate.…”
Section: Discussionmentioning
confidence: 91%